s-Proline Covalented Silicapropyl Modified Magnetic Nanoparticles: Synthesis, Characterization, Biological and Catalytic Activity for the Synthesis of thiazolidin-4-ones - Fekri, Leila Z. (Current Organic Synthesis, 2020)
Background: Thiazolidinoneones are important pharmaceutical compounds because of their biological activities. Several methods for the synthesis of 4-thiazolidinones are widely reported in the literature. The main synthetic routes to synthesize 1,3-thiazolidin-4-ones involve three components reaction between amine, a carbonyl compound and thioglycolic acid. Objective: s-Proline covalented silicapropyl modified magnetic nanoparticles (Fe3O4@SiO2-Pr @s-proline) were prepared. The antibacterial activity of synthesized nanoparticles against four bacterias was investigated that showed that 30 Mg/L of synthesized nanoparticles is a suitable concentration for bacterial inhibitory. Finally, the catalytic application of the synthesized s-Proline covalented silicapropyl modified magnetic nanoparticles for the synthesis of thiazolidinones and pyrazolyl thiazolidinones under stirring in aqueous media was evaluated. All of the synthesized organic compounds were characterized by mp, FT IR, 1H NMR, 13C NMR and elemental analysis. Materials and Methods: A combination of aldehyde (1.0 mmol), thioglycolic acid (1.0 mmol), various amines (1mmol) and 0.05 g Fe3O4@SiO2propyl@L-proline, were reacted at room temperature under stirring in 10 mL water. After completion of the reaction, as indicated by TLC (4:1 hexane: ethylacetate), the reaction mixture was filtered in the presence of an effective magnetic bar to separate the nanocatalyst. The nanocatalyst was washed with a mixture of hot EtOH: H2O two times. The crude products were collected and recrystallized from ethanol, if necessary. Results and Discussion: We present a novel avenue for the synthesis of thiazolidinones in the presence of Fe3O4@SiO2-Pr @s-proline under solvent-free conditions. Conclusion: In conclusion, we have synthesized Fe3O4@SiO2-Pr@s-proline nanoparticles. Their biological activity against 4 bacterias was investigated. It released that 30Mg/L is the suitable concentration of synthesized nanoparticle for bacterial inhibitory. The catalytic efficiency of the catalyst was checked in the multicomponent reaction of various aldehyde, thioglycolic acid and various amines under stirring. This nanoparticle is a new organic-inorganic hybrid nanoparticle. The operational simplicity, the excellent yields of products, ease of separation and recyclability of the magnetic catalyst, waste reduction and high selectivity are the main advantages of this catalytic method. Furthermore, this new avenue is inexpensive and environmentally benign.
Keywords: Fe3O4@SiO2-propyl@s-proline